PERANCANGAN MESIN PENCUCI KERANJANG INDUSTRI DI PT. BERDIKARI METAL ENGINEERING - Muharramin, Areza; Samosir, Reguel; Napitupulu, Robert; Haritsah Amrullah, Muhammad (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Industrial crate washing is a crucial activity in maintaining hygiene and operational efficiency within the manufacturing sector. PT. Berdikari Metal Engineering faces challenges due to a manual washing process that is labor-intensive, time-consuming, and only capable of cleaning 25 crates per day out of a 150-crate target. This study aims to design an automatic crate washing machine with a focus on high-pressure washing systems to enhance process effectiveness. The design method follows the VDI 2222 approach, consisting of planning, conceptualization, design, and simulation stages. The machine features three main zones: washing, rinsing, and drying, where washing and rinsing utilize a jet pump system. Technical calculations determined that the required motor pump power for the washing zone is 10 HP, based on the number of nozzles, flow rate, and spray pressure of 80 psi. Simulation results using SolidWorks indicate that the machine structure is safe, with stress and safety factor values within acceptable limits. In conclusion, the design successfully delivers an efficient washing system that meets the company's daily production targets and reduces reliance on manual labor.